Living on The Edge: Survival Strategies of Millennial and Gen Z Under Low Minimum Wages in The Yogyakarta Special Region - Amalia, Siti; Kesuma, Agus Iwan (International Journal of Economics (IJEC), 2026)
The Yogyakarta Special Region (DIY) has set its 2025 Provincial Minimum Wage (PMW) at IDR 2,264,080.95, ranking as the third lowest nationwide, amid a steadily rising cost of living. This situation presents significant challenges for Millennial and Generation Z, who form the backbone of the local workforce. This study examines the dynamics of minimum wage policy implementation for young workers in DIY, focusing on the socioeconomic implications and adaptive strategies of workers in both formal and informal sectors. Using a qualitative approach with in-depth interviews of 20 informants representing diverse occupational and age backgrounds, the study identified five main themes: (1) consumption pattern adjustment, (2) income diversification, (3) social support and collectivity, (4) career aspirations and mobility, and (5) survival strategies rooted in local culture and community-based economy. Findings indicate that although the minimum wage policy aims to improve welfare, young workers in DIY continue to face substantial economic pressures due to the mismatch between wage levels and living costs. Adaptive strategies include consumption frugality, multiple job holding, utilization of digital platforms, and strengthening of community-based social networks. The phenomenon of “economic mutual aid” emerged as a form of social capital rooted in Javanese cultural values, functioning to reduce economic vulnerability through resource sharing, informal financial assistance, and service exchange. This study contributes to the literature on minimum wage policy by highlighting the importance of incorporating local context, social capital, and cultural norms. Policy implications include regional cost-of-living-based wage adjustments, strengthening of social protection, and empowerment of community-based economic initiatives.